Systematic review of birth cohort studies in Africa - Alasdair Campbell; Igor Rudan (Edinburgh University Global Health Society, 2011)
In sub-Saharan Africa, unacceptably high rates of mortality amongst women and children continue to persist. The emergence of research employing new genomic technologies is advancing knowledge on cause of disease. This review aims to identify birth cohort studies conducted in sub-Saharan Africa and to consider their suitability as a platform to support genetic epidemiological studies.